Antenatal myomectomy: is it safe? - Nor Amirawati A,; Anizah Ali,; Shafiee MN, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Myomectomy is rarely performed in pregnancy due to risk of miscarriage or pregnancy loss, bleeding and possible hysterectomy. Myomectomy is mainly reserved for unavoidable indications such as rapidly growing fibroid or severe pain with possiblity of red degeneration for which medical treatment failed. However, good outcome had been reported in selective second trimester myomectomies.